Respuesta :

Answer:

[tex]t=\frac{p}{s_1-s_2}[/tex]

Step-by-step explanation:

Assuming the "1" and "2" are subscripts, we can write the problem as following:

[tex]p=s_1t-s_2t[/tex]

In order to solve for t, we need to isolate it first and then do algebra. The steps are shown below:

[tex]p=s_1t-s_2t\\p=t(s_1-s_2)\\t=\frac{p}{s_1-s_2}[/tex]

Answer:

[tex]t=\frac{p}{(s_1-s_2)}[/tex]

Step-by-step explanation:

We have been given an equation [tex]p=s_1t-s_2t[/tex]. We are asked to solve our given equation for t.

First of all, we will factor out t from right side of our given equation as:

[tex]p=t(s_1-s_2)[/tex]

Now, we will switch sides as:

[tex]t(s_1-s_2)=p[/tex]

Finally, we will divide both sides of our equation by [tex](s_1-s_2)[/tex].

[tex]\frac{t(s_1-s_2)}{(s_1-s_2)}=\frac{p}{(s_1-s_2)}[/tex]

[tex]t=\frac{p}{(s_1-s_2)}[/tex]

Therefore, the value of t for our given equation would be [tex]\frac{p}{(s_1-s_2)}[/tex].